Influence of Steryl Esters on the Delivery of Polycyclic Aromatic Hydrocarbons in Tobacco Mainstream Smoke - Du, You; Liu, Hailong; Xue, Fang; Fu, Haiyan; Dai, Ya; Li, Dongliang; Chen, Hua (Asian Journal of Chemistry, 2013)
Steryl esters, stigmasteryl oleate, cholesteryl oleate and b-sitosteryl oleate were synthesized and used as an additive in the cigarettes for studying the influence on the delivery of polycyclic aromatic hydrocarbons by GC-MS. The results showed that the delivery of polycyclic aromatic hydrocarbons in tobacco mainstream smoke was closely related to the addition levels of those steryl esters, indicated that the steryl esters are possible the most potential precursors of polycyclic aromatic hydrocarbons in tobacco mainstream smoke.